BGP design and implementation, - Zhang, Randy; Bartell, Micah
BGP Design and Implementation focuses on real-world problems and provides not only design solutions, but also the background on why they are appropriate and a practical overview of how they apply into a top-down design. The BGP protocol is being used in both service provider and enterprise networks. The design goals of these two groups are different, leading to different architectures being used in each environment. The title breaks out the separate goals, and resulting solutions for each group to assist the reader in further understanding different solution strategies. This book starts by identifying key features and functionality in BGpáginas: It then delves into the topics of performance tuning, routing policy development, and architectural scalability. It progresses by examining the challenges for both the service provider and enterprise customers, and provides practical guidelines and a design framework for each. BGP Design and Implementation finishes up by closely looking at the more recent extensions to BGP through Multi-Protocol BGP for MPLS-VPN, IP Multicast, IPv6, and CLNS. Each chapter is generally organized into the following sections: Introduction, Design and Implementation Guidelines, Case Studies, and Summary.